PENGARUH PEMBERIAN MEAL REPLACEMENT TINGGI PROTEIN KEDELAI TERHADAP : Berat Badan, Persen Cairan Tubuh, Dan Persen Lemak Tubuh Pada Dewasa Obesitas Di AVR Fit Nutrition Club - Fauziyyah Hana Chaerani (2020)
Obesity related to the accumulation of body fat which results increasing body weight and body composition such as: body water, and body fat percentage. A diet high soy protein can suppress food intake and regulate satiety and emptying of the stomach for longer. This research was conducted to analyze the effect of high protein soybean meal replacement feeding on body weight, body water percentage, body fat percentage in obese adults. The research is an experimental research with Pre-Post Test Without Control design. Subjects were obese adults aged 18-50 years, BMI (≥30kg / m2) and exclusion criteria were no slimming drugs, and were not undergoing weight loss and fat loss treatment through special therapy (laser, acupuncture, surgery, etc.). The intervention period was carried out for 30 days. Measurements were carried out using the BIA (Bio-electrical Impedance Analysis) scale of the Tanita brand. Analyzes were performed using the Paired Sample T-test and Wilxocon test. Wilxocon test results show that there is a significant influence of high protein soybean meal replacement giving (p <0.05) on body weight. In addition, the results of the Sample T-test also showed a significant effect (p <0.05) on body water percent and body fat percent. This study shows the effect of giving high protein soybean meal replacement that are high in protein to weight loss, increase in body water percent, and decrease in body fat.